STEM/Non-STEM Divide Structures Undergraduate Beliefs About Gender and Talent in Academia - Bailey, Kimberlyn A.; Horacek, David; Worthington, Steven; Nanthakumar, Ampalavanar; Preston, Scott; Ilie, Carolina C. (Frontiers in Sociology, 2019)
Research and popular debate on female underrepresentation in academia has focused on STEM fields. But recent work has offered a unifying explanation for gender representation across the STEM/nonSTEM divide. This proposed explanation, called the fieldspecific ability beliefs (FAB) hypothesis, postulates that, in combination with pervasive stereotypes that link men but not women with intellectual talent, academics perpetuate female underrepresentation by transmitting to students in earlier stages of education their beliefs about how much intellectual talent is required for success in each academic field. This theory was supported by a national survey which found that the disciplines with the fewest women had practitioners who were most likely to think that success in their field requires [talent]/[brilliance]. We test this topdown schema with a nationwide survey of U.S. undergraduates, assessing the extent to which undergraduate beliefs about talent in academia mirror those of academics. We find no evidence that academics transmit their beliefs to undergraduates. We also use a second survey – identical to the first but with each field’s gender ratio provided as added information – to explicitly test the relationship between undergraduate beliefs about gender and talent in academia. The results for this second survey suggest that the extent to which undergraduates rate brilliance as essential to success in an academic field is highly sensitive to this added information for nonSTEM fields, but not STEM fields. Overall, our study offers evidence that, contrary to FAB hypothesis, the STEM/nonSTEM divide principally shapes undergraduate beliefs about both gender and talent in academia.